2019
DOI: 10.1002/adfm.201905529
|View full text |Cite
|
Sign up to set email alerts
|

2D Hybrid Perovskite Ferroelectric Enables Highly Sensitive X‐Ray Detection with Low Driving Voltage

Abstract: X-ray detectors with high sensitivity are of great significance in both civil and military fields. Over the past decades, great efforts have been made to improve the sensitivity in conventional inorganic materials, but mainly at the cost of increasing the energy consumption with a quite high operating voltage. Developing photosensitive ferroelectrics directly as detector materials may be a conceptually new strategy in view of the strong ferroelectric spontaneous polarization (P s ) that assists photoinduced ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
152
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(154 citation statements)
references
References 42 publications
(62 reference statements)
2
152
0
Order By: Relevance
“…[ 1–3 ] Recently, metal halide perovskites and their derivatives have achieved great successes as direct X‐ray detectors. [ 4–8 ] The heavy atoms (Pb, Bi), good carrier transport and long carrier lifetime of the materials together contribute to the excellent detection performance. [ 4–6 ] Huang and co‐workers reported that MAPbBr 3 ‐based X‐ray detectors demonstrate high sensitivity of 21000 μC Gy air −1 cm −2 and low detection limit of 38 nGy air s −1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1–3 ] Recently, metal halide perovskites and their derivatives have achieved great successes as direct X‐ray detectors. [ 4–8 ] The heavy atoms (Pb, Bi), good carrier transport and long carrier lifetime of the materials together contribute to the excellent detection performance. [ 4–6 ] Huang and co‐workers reported that MAPbBr 3 ‐based X‐ray detectors demonstrate high sensitivity of 21000 μC Gy air −1 cm −2 and low detection limit of 38 nGy air s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] Besides, some newly derived ferroelectric perovskite and metal‐organic frameworks also exhibited good potential for X‐ray applications. [ 7,8 ]…”
Section: Introductionmentioning
confidence: 99%
“…Alternative materials based on double perovskites [12][13][14][15] and low-dimensional perovskites [15][16][17][18][19][20] are also being explored as they enrich the structural diversity and property repertoire of the perovskite framework. The 3D perovskite structure which forms by the corner-sharing motif of the MX 6 octahedra of Pb 2+ and Sn 2+ creates a favorable electronic band structure with very broad valence and conduction bands which facilitate photo-excited charge transport.…”
Section: Introductionmentioning
confidence: 99%
“…[ 33–39 ] Especially, they have high atomic number ( Z ) and high‐quality elements, such as Pb, Br, and I atoms. [ 40–45 ] Because the cross‐section of halide perovskite increases with the increase of ≈ Z 4 , which makes it to naturally have good ionizing radiation absorption ability. In addition, halide perovskites exhibit inherent high carrier mobility, long carrier lifetime, high stopping power, low detection limit, and polychromatic radioluminescence (RL), which make them possess the capability for radiation detection.…”
Section: Introductionmentioning
confidence: 99%